Дослідження ефективності управління примежовим шаром на опорній поверхні шляхової структури перспективних транспортних технологій Maglev - Заславський, Б.Л.; Сохацький, А.В. (Геотехническая механика, 2012)
Исследованы физические процессы управления пограничным слоем на профилированной поверхности путевой структуры перспективных транспортных технологий. Установлены закономерности влияния параметров управления пограничным слоем на распределение скоростей на путевой структуре. The physical processes of control are investigational by a frontier layer on the profiled surface
of the ground structure of perspective transport technologies. Conformities to law of influence of
control parameters are set by a frontier layer on distribution of speeds on the ground structure.